Experimental study on physical and mechanical characteristics of rock-concrete combined body under complex stress conditions. (21st March 2022) - Zhao, Yu; Shen, Mingxuan; Bi, Jing; Wang, Chaolin; Yang, Yongtao; Du, Bin; Ning, Lin
Highlights: Tidal waves and vehicle loadings effect loaded above pile foundations of bridges is represented the complicated stress load scheme in coastal areas. The physical and mechanical characteristics of rock-concrete specimens under complicated stress paths are studied. The failure mode of rock-concrete specimens gradually translates mainly shear failure from slipping failure with the decrease of roughness. The changes in the roughness of rock-concrete specimens leading to the irreversible strain of rock-concrete combined body produce differences. Abstract: Tidal waves and vehicle loadings forming a complex stress condition in coastal regions have a significant effect on the stability of engineering structures. It is therefore necessary to understand the physical and mechanical behaviors for rock-concrete combined structures under complex stress conditions for realizing the safe design of structures. Therefore, the complex stress condition tests of rock-concrete samples of varying roughness are performed in this study. The stress–strain curves of the rock-concrete samples show that hysteresis occurred under complex stress conditions. As the confining pressure increases, the hysteresis loop area increases. Furthermore, the elastic modulus increases accordingly as the roughness increases. The lateral deformation ratio ( κ ) of the loaded rock-concrete sample increases as the number of cycles increases, but decreases as the height of roughness increases. The Mohr-Coulomb (M−C) criterion and the Hoek-Brown (H-B) criterion are used to fit the testing data and for discussion. The H-B strength criterion is suitable for describing the strength characteristics of the rock-concrete combined body under complex stress conditions. Ultimately, with the increasing axial loading and decreasing confining loading, the relative slipping on the adjacent triangle rock base and concrete resulted in the occurrence of the tensile crack.